Complement gene mutations in children with C3 glomerulopathy: Do they affect the response to mycophenolate mofetil - GÖKCE, İBRAHİM; ÇİÇEK DENİZ, NESLİHAN; ALPAY, HARİKA (My University, 2023)
Background: C3 glomerulopathy (C3G) is a complement-mediated disease. Although genetic studies are not required for diagnosis, they are valuable for treatment planning and prognosis prediction. The aim of this study is to investigate the clinical phenotypes, kidney survival, and response to mycophenolate mofetil (MMF) treatment in pediatric C3G patients with and without mutations in complement-related genes. Methods: Sixty pediatric C3G patients were included, divided into two groups based on complement-related gene mutations. Demographic and clinical-pathological findings, treatment modalities, and outcome data were compared, and Kaplan–Meier analysis was performed for kidney survival. Results: Out of the 60 patients, 17 had mutations. The most common mutation was in the CFH gene (47%). The mean age at diagnosis was higher in the group with mutation (12.9 ± 3.6 vs. 11.2 ± 4.1 years, p = 0.039). While the patients without mutation most frequently presented with nephritic syndrome (44.2%), the mutation group was most likely to have asymptomatic urinary abnormalities (47.1%, p = 0.043). Serum parameters and histopathological characteristics were similar, but hypoalbuminemia was more common in patients without mutation. During 45-month follow-up,10 patients progressed to chronic kidney disease stage 5 (CKD5), with 4 having genetic mutation. The time to develop CKD5 was longer in the mutation group but not significant. MMF treatment had no effect on progression in either group. Conclusions: This study is the largest pediatric C3G study examining the relationship between genotype and phenotype. We showed that the mutation group often presented with asymptomatic urinary abnormalities, was diagnosed relatively late but was not different from the without mutation group in terms of MMF treatment response and kidney survival. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health; C3 glomerulonephritis; C3 glomerulopathy; Children; Complement system; Genetic; Rare disease